Breaking resistance to nanoantibiotics by overriding corona-dependent inhibition using a pH-switch. (June 2019) - Siemer, Svenja; Westmeier, Dana; Vallet, Cecilia; Steinmann, Jörg; Buer, Jan; Stauber, Roland H.; Knauer, Shirley K.
Graphical abstract: In this work, we demonstrate that nanoantibiotics' activity depends on their binding to pathogens. Low pH NP-formulations electrostatically enhance complex formation, overriding the inhibitory impact of biomolecule coronas relevant for practical applications. We illustrate, which environmental factors influence NP–pathogen interaction. At pH <7, the pathogens' negative surface charge is lowered due to protonation of surface molecules, increasing electrostatic interactions of corona-covered NPs with bacterial surfaces. Abstract: Nanoparticles are investigated as novel antibiotics, but are often inefficient in practical applications. We show from in situ to in vitro to in vivo that the bactericidal activity of metal-based nanoparticles but not microparticles against multidrug-resistant clinical isolates (MDR) strongly depends on physical binding to pathogens. Using controllable nanoparticle models, we report that nanoparticle–bacteria complex formation was enhanced by small nanoparticle size rather than material or charge. However, nanoparticles' binding and thus antibiotic activity were concentration-dependently reduced by biomolecule coronas, acquired in pathophysiological environments, such as wounds or blood, causing bacterial resistance. Complex formation and MDR killing could however be restored by low-pH nanoparticle formulations, breaking bacterial resistance. Mechanistically, interaction of negatively charged, human plasma corona-covered, metal-based nanoparticles with pathogends was electrostatically enhanced by lowering pH-dependently bacteria's negative surface charge. Using two independent in vivo models, Galleria mellonella and mice, low pH-induced complex formation was critical to significantly inhibit MDR Staphylococcus aureus skin wound infections by silver nanoparticles. We here identified the first resistance mechanism specific for nanoantibiotics, provide an explanation why nanoantibiotics show reduced activity in clinically relevant environments, and a simple though effective way to boost nanoantibiotics' bactericidal activity for practical applications.